Ippolit Bogdanovich and Voltaire’s 'Épître à l’impératrice de Russie': Adapting Praise - Andrew Kahn (Modern Languages Open)
The age of Catherine the Great was also the great age of Russian court poetry. Praise for the monarch, written by scientists, physicians, men (and women) of letters, trumpeted a standard set of virtues attributed to the Minerva of the North. If the ideological content of poems and especially the ode was not formally prescribed, the conventions of panegyric and rhetorical flourishes nonetheless imposed formulaic content. Writers bent on delivering a specific message understood that giving advice was not a straightforward matter, resorting to the arts of praise to create the illusion that everything suggested was already acceptable to the enlightened monarch. Ippolit Bogdanovich was one of the most versatile poets of the period, appreciated for his original compositions and recognised for his adaptations of French poetry. He was also one of the most adept at the graceful packaging of didactic themes or conveying a policy suggestion. This essay considers how his translation of Voltaire’s Épître à l’impératrice de Russie (1771) reworks a famous poem of praise. Adaptation of a foreign work proves to be an opportunity to exploit well-received tropes in the service of a subtle change of message. Within its conventional duty to praise, Bogdanovich’s rewriting of Voltaire shifts the emphasis away from the theme of Orientalism and Catherine’s Turkish Wars to the benefits of reason and civilisation. The effect is to present a different perspective on the value of the empress’s achievements, offering praise but also implicitly a challenge to her to be better than Voltaire’s more militaristic portrait would have her be.